Longitudinal cleavage of the penis in chronic spinal cord injury: two case reports. (3rd May 2016) - Mansoor, Sahibzada Nasir; Ayaz, Saeed Bin; Rathore, Farooq Azam; New, Peter
Abstract : Context: Penile cleavage is a rare complication of spinal cord injury (SCI) in patients with a chronic indwelling catheter. We report two cases of chronic SCI who developed penile urethral cleavage after prolonged use of an indwelling catheter for bladder management. Findings: A 25-year-old wheelchair mobile male with T7 American Spinal Injury Association (ASIA) Impairment Scale (AIS) grade A paraplegia developed a 4 × 1.5 cm ventral urethral cleavage after using an indwelling catheter for four months with inadequate care. He had an associated urinary tract infection and undiagnosed diabetes mellitus. A suprapubic catheter was inserted and surgical repair recommended after resolution of UTI and adequate control of his diabetes mellitus. After initial treatment he was lost to follow-up. The second patient was a 15-year-old male with AIS grade B tetraplegia who presented with a 2.5 cm cleavage on the ventral aspect of penis for the preceding three months. He had been using an indwelling catheter for bladder management for the previous 18 months. He had modified Ashworth scale grade III spasticity in lower limbs resistant to conservative management. There was no history of trauma, infection or diabetes mellitus. The patient was advised penile urethral repair surgery but was lost to follow-up. Conclusion: Penile cleavage is a rare complication of neurogenic bladder in SCI patients. Patients and care givers should be trained in proper bladder management techniques during the hospital stay, counseled regarding the need for regular follow up, and be taught identification and prevention of common complications.